Nutrient Management in High Density Cashew Plantation under Coastal Zones of Odisha - Tripathy, P.; Sethi, K.; Patnaik, A. K.; Mukherjee, S. K. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Cashew Research Station of AICRP on Cashew, OUAT, Bhubaneswar, Odisha, India during 2000 to 2013 study about the effect of different plant density with different dose of fertilizer on growth and yield of cashew variety BPP 8 (H 2/16). The experiment was laid out in a split plot design with three planting densities [10×5 m2 (200 plants ha-1; 6×4 m2 (400 plants ha-1) and 5×4 m2 (500 plants ha-1)] along with three levels of fertilizer (75-25-25, 150-50-50 and 225- 75-75 kg NPK ha-1) replicated four times. The results revealed that adoption of high density planting system significantly decreases the tree height (5.71), stem girth (69.16 cm), number of flowering laterals m-2 (4.52), nuts panicle-1 (7.63), nut weight (7.6 g), cumulative yield at 11th harvest (26.77 kg tree-1) than wider spacing of 200 plants ha-1. Similar trends were observed for fertilizer dose of 150-50-50 kg ha-1 for all the parameters under study, irrespective of plant densities. However maximum cumulative yield of 15,140.50 kg ha-1 with BCR of 3.04, closely followed by 14,052.05 kg ha-1 with BCR of 2.61 was observed at high density planting (500 plants ha-1) and moderately to high fertilizer dose (150-50-50 to 225-75-75 kg NPK ha-1) over 11th harvest of cashew under Odisha condition. The study also indicated that, in case of high density planting system, pruning should be done after 5th harvest while 8th harvest in wider spacing in order to maintain the productivity of plants at optimum levels.